AUGMENTED REALITY TECHNOLOGY FOR VISUALIZING DIPANEGARA UNIVERSITY BUILDINGS - Josseano Amakora Koli Parera; Tommy Maulidyanto (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Multimedia technology continues to advance, one of which is Augmented Reality (AR) technology, commonly known as the technology for merging virtual objects into the real world. Building brochures, which only display building photos and are visible from only one side, require us to visit the building to view its structure. Therefore, an idea emerged for a design of an application that uses Android-based Augmented Reality technology. This application allows users to view a more realistic physical shape of the building without visiting it directly by directing the camera towards a marker displaying the building's logo and showing a 3D model of the Dipanegara University building. It also provides general information about the building. This application is designed using 3DS Max, Unity, and Vuforia SDK, making it easier for prospective students to view the building's layout. Keywords : 3DS Max, Android, Augmented Reality, Unity, Visualization.